Tertiary students in Singapore : the link between financial knowledge and habits. - Chua, Si Min. (2008)
With the potential increase in spending power upon graduation, tertiary students represent a lucrative market for financial institutions to venture into. This paper therefore investigates the financial habits of tertiary students and the relationship between habits and financial knowledge, thereby helping financial institutions gain a deeper insight of the market.